PENGARUH TINGKAT SUKU BUNGA DAN NILAI TUKAR RUPIAH TERHADAP RETURN SAHAM - Nanok Fitriyadi S (Jurnal Eksis, 2020)
AbstractThe food and beverage sub-sector on the IDX was also affected by the growth of investment activities carried out by young people, based on data from the Ministry of Industry the increase in this sector reached 192.69 T in the third quarter of 2016. Every investment activity carried out, of course, there are factors that affect the results Of these activities. There are fundamental factors (micro) or internal factors and technical factors (macro) or external factors that play a role in determining the results of the investment made. By knowing these two factors, the return or investment results made can be slightly analyzed so as to reduce the risk that may occur. The purpose of this study is to determine how much influence the interest rate and the rupiah exchange rate have on stock returns in manufacturing companies listed in the food and beverage sub-sector. BEI 2013 - 2018. This research was conducted with a population of 24 companies, using purposive sampling data collection technique, the sample size was 13 companies. For the data analysis technique, hypothesis testing was carried out using multiple linear regression and hypothesis testing. The results showed that the interest rate had a negative and significant effect on stock returns with a significance value of 0.012, the rupiah exchange rate had a negative and significant effect on stock returns with a significance value of 0.019, and the interest rate and the rupiah exchange rate simultaneously had a significant effect on stock returns. In the food and beverage sub-sector manufacturing companies listed on the IDX in 2013-2018 with a significance value of 0.016. Theoretically, this research is useful for increasing knowledge related to the factors that trigger stock returns on the IDX, practically this is a reference for investors who will or have invested in stocks.